Mass spectrometric investigation of amorphous Ga-Sb-Se thin films - Mawale, Ravi; Halenkovič, Tomáš; Bouška, Marek; Gutwirth, Jan; Nazabal, Virginie; Bora, Pankaj Lochan; Pecinka, Lukas; Prokes, Lubomir; Havel, Josef; Němec, Petr (Nature Publishing Group, 2019)
Amorphous chalcogenide thin films are widely studied due to their enhanced properties and extensive applications. Here, we have studied amorphous Ga-Sb-Se chalcogenide thin films prepared by magnetron co-sputtering, via laser ablation quadrupole ion trap time-of-flight mass spectrometry. Furthermore, the stoichiometry of the generated clusters was determined which gives information about individual species present in the plasma plume originating from the interaction of amorphous chalcogenides with high energy laser pulses. Seven different compositions of thin films (Ga content 7.6-31.7 at. %, Sb content 5.2-31.2 at. %, Se content 61.2-63.3 at. %) were studied and in each case about -50 different clusters were identified in positive and -20-30 clusters in negative ion mode. Finally, for selected binary and ternary clusters, their structure was calculated by using DFT optimization procedure.
Studium amorfních tenkých vrstev Ga-Sb-Se pomocí hmotnostní spektrometrie
Keywords: amorphous chalcogenides; thin films; magnetron sputtering; mass spectrometry; amorfní chalkogenidy; tenké vrstvy; magnetronové naprašování; hmotnostní spektrometrie